Who Makes Your Heart Beat? What Makes You Sweat? Social Conflict in Virtual Reality for Educators - Lee, Minha; Kolkmeier, Jan; Heylen, Dirk; IJsselsteijn, Wijnand (Frontiers in Psychology, 2021)
Though educators often deal with stressful social conflicts, many face them ad hoc without much training. We studied if and how virtual agents can help university staff manage student-teacher conflicts. We explored educators' verbal, behavioral, and physiological reactions to a virtual agent that brought up a student-teacher conflict and held exit-interviews. Our qualitative analysis revealed that virtual agents for conflict training was positively received, but not for conflict mediation with cross-cultural differences. Those with non-Western backgrounds felt that an agent could help \say{save face}, whereas Westerners preferred to resolve conflicts in person. In line with this, participants with a Western background rated the virtual agent to be less competent compared to those with non-Western backgrounds. While physiological measures only allow for limited conclusions, we found that participants who believed that the agent was controlled by a human had higher normalized hear rate variability (for the entire conversation in total) than people who thought that the agent was autonomous. We discuss implications for implementing virtual agents for training purposes, the impact physiological signals, and the need to consider cultural and individual differences.